Morphometric Characteristics and Species Identification of Bed Bugs (Hemiptera: Cimicidae) in Eastern Iran - Abbas Jadidoleslami; Ali Moshaverinia; Elham Moghaddas; Veera Singham (Tehran University of Medical Sciences, 2024)
Background: The common bed bugs, Cimex lectularius, and tropical bed bugs, Cimex hemipterus are the primary species of public health importance in the family Cimicidae. This study aimed to determine the morphometric criteria and prevalent species of bed bugs in eastern Iran. Methods: Bed bugs were collected from March 2021 to June 2022 from infested residential buildings and apartments in eastern Iran, including North Khorasan, Khorasan Razavi, and Sistan and Baluchistan Provinces. The morphological and morphometrical characteristics were used to identify collected bed bugs at inter- and intra-specific levels. Results: A total of 34 isolates comprising 127 adult bed bugs were collected from Bojnord, Mashhad, Neishabur, Taibad, Sabzevar, Kashmer, Zahedan, Saravan, Rask, Pishin and Chabahar. Of these, 33 isolates (n=124) were found to be tropical bed bugs, C. hemipterus, and one population (n=3) was identified as C. lectularius. The index pronotal width/length ratio was calculated from 2.72 to 2.94 and 1.98 to 2.47 for C. lectularius and C. hemipterus, respectively. The length/width ratio of the hind femur was 3.365 in C. hemipterus and 4.267 in C. lectularius. The ratio of length/width of the third femur (F3 l/w) between populations of C. hemipterus was different, and this difference was statistically significant (P< 0.05). Conclusion: The results of this study indicated that C. hemipterus was the dominant bed bug species in the east of Iran and provided more morphometric criteria of C. hemipterus for researchers to identify the species and determine the intraspecific variations in the present and future.